Региональные сдвиги эндогенной продукции оксида азота в цитозоле и митохондриях тканей головного мозга крыс при депрессивноподобном состоянии, индуцированном хроническим стрессом - Н. С. Назарян (Հայաստանի ԳԱԱ)
Համաձայն ժամանակակից պատկերացումների` գլխուղեղում ընկճվածության ժամանակ առաջանում են շեղումներ ազոտի օքսիդի (NO) ներսածին գոյացման գործընթացի մեջ: Ներկայացված աշխատանքում առաջին անգամ պարզաբանվել է վերջերս հայտնաբերված միտոքոնդրիումային ազոտի օքսիդի սինթազի (NOS) ներգրավումը ընկճման մոլեկուլային մեխանիզմներում: Depression is associated with the changes in L-arginine-dependent nitric oxide (NO) production in the brain. We have studied for the first time whether recently discovered mitochondrial NO synthase (NOS) is involved in the pathophysiological mechanisms of depression and demonstrated that chronic circadian stress (CCS)-induced depression-like behavior of rats is accompanied by an upregulation of inducible NOS (iNOS) and a simultaneous downregulation of constitutive NOS isoforms (cNOS) in both cytosolic and mitochondrial compartments of prefrontal cortex (PFC),striatum, hippocampus, and hypothalamus, the major brain regions involved in the regulation of anticipatory chronic stress responses.
Keywords: Medicine; Internal medicine; Neuroscience; Biological psychiatry; Neuropsychiatry